Status Breast condition and Babies Health Influence Practice of Exclusive Breastfeeding - Kistina Marieta Baby Solo; Regina Vidya Trias Novita (Universitas Muhammadiyah Semarang, 2020)
The fluctuation of the number on three years who had a practice of breastfeeding exclusively at Kupang. There was stagnant for a number. The research aims to investigate the relationship between factors and practices of exclusive breastfeeding at the Primary Health of Alak in Kupang. The study was quantitative research with a descriptive correlation design and used a retrospective approach. The analysis data using Chi-Square with samples of this research were 275 mothers, in which they were taken through purposive sampling, and held on August-September 2016. Data were collected using questioners. The result shows that there was a correlation between some factors and breastfeeding practices, which were the mother’s occupation (p-value =0,036), conditions of their breast (p-value = 0,002), and the babies’ health (p-value = 0,006). Giving solutions for the problem that the mother faces during breastfeeding make the mother have the confidence to sustaining breastfeeding until two years. Nurses have competent to help mothers especially for positions, latch on and expressing the milk for worker mother, problem breast, and when the baby was sick.